HUBUNGAN GAYA KEPEMIMPINAN KEPALA SEKOLAH DENGAN KINERJA GURU DI SD NEGERI SE-KECAMATAN SIMPANG EMPAT - Tri Widya Ningsih; Erlinda Simanungkalit; Masta Marselina Sembiring; Dila Handayani (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to determine the relationship between the principal's leadership style and teacher performance in public elementary schools in Simpang Empat District. The research method is correlation. The sample of this research is using purposive sampling technique, so the sample of this research is the teachers of SD Negeri Se-District Simpang Empat who have civil servant status, totaling 33 people. The results showed that the leadership style of the principal of the SD Negeri in Simpang Empat was categorized as moderate with an average score of 74.42. Meanwhile, the performance of elementary school teachers in Simpang Empat sub-district is in the sufficient category with an average score of 102.45. Furthermore, there is a relationship between the principal leadership style variable (X) and the teacher performance variable (Y) with rcount > rtable with a value comparison of (0.437 > 0.344). This shows that there is a positive relationship between the principal's leadership style and the performance of public elementary school teachers in the Simpang Empat District which has a moderate level of correlation. Then the t-test obtained tcount of 2,689 while ttable obtained from the critical list in the table against = 0.05 of 2,039 means tcount > ttable with a comparison value of (2,689 > 2.039) so Ha is accepted and H0 is rejected.Keywords: Principal Leadership Style, Teacher Performance.